Topology Control and Medium Access Control (MAC) Protocol for Wireless Sensor Networks (WSNs) in Cyber-Physical System. (3rd May 2021) - Li, Ang; Zhang, Chen; Zheng, Baoyu; Li, Lei
Abstract : The system reachability set is calculated by covering all possible behaviours of the system through a finite number of simulation steps to ensure that the system trajectory stays within a set safety region. In this paper, the theory of the game method is applied to the design of the controller, a very small controller is designed, and good control results are obtained by simulation. The system gradually shows a divergent trend and cannot achieve stable control. A multihop channel reservation Medium Access Control (MAC) protocol based on a parallel mechanism is proposed. The multihop channel reservation mechanism is proposed based on periodic node sleep, and the node uses the reservation frame to make the reservation of the channel and transmits the data according to the reservation information; the parallel mechanism is used to make the reservation information and data transmission simultaneously.